Pemberdayaan Usaha Mikro Kecil dan Menengah melalui Transfomasi Digital E-Commerce di Desa Ngloning Kabupaten Ponorogo - Parwi; Fajar Satriyawan Wahyudi; Riyanmar Fayat Zabihullah (Yayasan Tajuk Indonesia, 2025)
MSME Kripik Corn chips in Ngloning Village, Ponorogo, is one of the local products that has great potential but still faces obstacles in marketing. that has great potential but still faces obstacles in digital marketing. digital marketing. This research aims to increase product sales through implementation of a more effective e-commerce strategy. The approach usedis training and mentoring related to online store creation, product packaging, and the use of digital platforms for marketing, packaging, and the use of digital platforms for marketing. The results showedan increase in sales of up to 30% as well as more independent business management skills. more independent business management skills.